Why David Sometimes Wins: Leadership, Organization, and Strategy in the California Farm Worker Movement - Keith, Sheldon (Relations industrielles / Industrial Relations, 2010)
Why David Sometimes Wins: Leadership, Organization, and Strategy in the California Farm Worker Movement, by Marshall Ganz, is reviewed.
Keywords: Book reviews; Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Farmworkers; Labor Unions; Leadership; Opportunity; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z; Strategic management

Qu'est-ce que l'intégration ? - Keith, Sheldon (Relations industrielles / Industrial Relations, 2008)
The article reviews the book, "Qu’est-ce que l’intégration ?," by Dominique Schnapper.
Keywords: Business And Economics–Labor And Industrial Relations; Business And Economics–Personnel Management; Labor Unions; SnR_publicationTitle_Relations Industrielles_Relations industrielles / Industrial Relations_2025-09-22T16:07:02.081Z